AN ANALYSIS OF THE STRUCTURAL DYNAMICS OF RECENT POLITICAL SECULARISM IN TURKEY AND HABERMAS' PROPOSED REMEDIES - Hadi, Muhsin Abdul (SIYAR Journal, 2024)
Within the intricate structure of global political landscapes, the nation of Turkey emerges as a captivating subject of study, particularly when examining its progressive secularism and the complex interplay of socio-political dynamics. This study aims to examine the fundamental structural factors that surround the implementation of Turkey's present political secularism, while also employing Habermas' proposed notion of a post-secular society as an approach to address and resolve these intricacies. This study utilizes a qualitative research methodology by doing literature studies and relying on secondary data for data collection. The findings of this study suggest that Habermas's notion of a post-secular society has the potential to develop a sociopolitical structure that is more democratic and inclusive in the setting of Turkey where it is being investigated.